Interfaz para la evaluación de la estabilidad transitoria de un sistema eléctrico ante diferentes porcentajes de generación no convencional. (2019)
Currently, traditional generation companies are interested in knowing and understanding the impact of the incursion of non-conventional energies into power systems. However, there is no tool that allows carrying out studies of the dynamic behavior of electric networks that incorporate these sources with the specificity and effectiveness that is needed. Therefore, a design and creation of a graphical user interface is proposed to facilitate the evaluation of the effect that this type of generation has on traditional energy systems, based on stochastic analysis and random characteristics given the variability of the resource from which the energy is extracted. Finally, it was statistically demonstrated that the relationship between the distribution of the critical fault clearing time and the non-conventional power penetration level is not trivial and a more detailed study is required in order to establish standards regarding the limits of non-conventional energy injection to guarantee the stability conditions of the system.